[Review of] traditional medicine in the colonial Philippines, 16th to the 19th century - Mallari, Aaron Abel T. (2018)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/7916/6904
Keywords: Books -- Reviews; Traditional medicine; Colonies